The Novel Phages phiCD5763 and phiCD2955 Represent Two Groups of Big Plasmidial Siphoviridae Phages of Clostridium difficile - Ramírez-Vargas, Gabriel; Goh, Shan; Rodríguez, César (Frontiers in Microbiology, 2018)
Until recently, C. difficile phages were limited to Myoviruses and Siphoviruses of medium genome length (32-57 kb). Here we report the finding of phiCD5763, a Siphovirus with a large extrachromosomal circular genome (132.5 kb, 172 ORFs) and a large capsid (205.6±25.6 nm in diameter) infecting MLST Clade 1 strains of Clostridium difficile. Two subgroups of big phage genomes similar to phiCD5763 were identified in 32 NAPCR1/RT012/ST-54 C. difficile isolates from Costa Rica and in whole genome sequences (WGS) of 41 C. difficile isolates of Clades 1, 2, 3, and 4 from Canada, USA, UK, Belgium, Iraq, and China. Through comparative genomics we discovered another putative big phage genome in a non-NAPCR1 isolate from Costa Rica, phiCD2955, which represents other big phage genomes found in 130 WGS of MLST Clade 1 and 2 isolates from Canada, USA, Hungary, France, Austria, and UK. phiCD2955 (131.6 kb, 172 ORFs) is related to a previously reported C. difficile phage genome, phiCD211/phiCDIF1296T. Detailed genome analyses of phiCD5763, phiCD2955, phiCD211/phiCDIF1296T, and seven other putative C. difficile big phage genome sequences of 131-136 kb reconstructed from publicly available WGS revealed a modular gene organization and high levels of sequence heterogeneity at several hotspots, suggesting that these genomes correspond to biological entities undergoing recombination. Compared to other C. difficile phages, these big phages have unique predicted terminase, capsid, portal, neck and tail proteins, receptor binding proteins, recombinases, resolvases, primases, helicases, ligases, and hypothetical proteins. Moreover, their predicted gene load suggests a complex regulation of both phage and host functions. Overall, our results indicate that the prevalence of C. difficile big bacteriophages is more widespread than realized and open new avenues of research aiming to decipher how these viral elements influence the biology of this emerging pathogen.